Morphological Characterization and Fusarium Wilt Resistance of Triploid Banana Mutant Line (Musa acuminata Cola) - Ishak, Ishak; Jumjunidang, Jumjunidang (AGRIVITA Journal of Agricultural Science, 2024)
Br 23 banana mutant line derived from irradiated gamma-ray from pisang ambon cultivar was triploid (AAA) and sterile. Therefore, application of conventional breeding to improve the agronomic characteristics of bananas requires strenuous effort. Morphological and agronomical characterizations of mutant line were observed during the generative stage on the Fusarium hotspot. Sixteen qualitative characters were observed, and each of which related to color was standardized using RHS color chart. Based on these qualitative characteristics, it was confirmed that pisang Ambon belongs to the acuminata group. Several agronomical characteristics of Br 23 banana mutant line, such as the number of hands/bunch, the weight of fruits/hand, and single fruit weight, were observed. The experimental results on banana production showed that the first harvest could reach 26 t/ha. Unlike from the control plant, the Br 23 mutant line showed tolerant characteristics to Fusarium TR4. The evaluation of susceptibility to Fusarium wilt was analyzed using the Vegetative Compatibility Group (VCG) method with isolate no. 01236/16. These susceptible plants were planted nearby the Br 23 banana mutant line. In early 2019, this Br 23 banana mutant line was registered as a new mutant variety under the name of PIRAMA I.